Analisis Hukum Perlindungan Konsumen Terhadap Ketidakfungsian Barcode Pada Tiket Konser Coldplay - Ananda, Via Rizky (Jurnal Ilmiah Wahana Pendidikan, 2024)
This journal aims to analyze the legal aspects of consumer protection related to the non-functionality of barcodes on Coldplay concert tickets. Technological developments in ticket booking systems have had a significant impact on the consumer experience, but often technical problems, such as barcode malfunctions, cause inconvenience and financial losses for consumers. The legal analysis in this journal is focused on reviewing consumer rights related to receiving goods or services in accordance with the contracts that have been made. In this context, the effectiveness of legal protection for consumers who face the problem of barcodes on concert tickets is the center of attention. This study also considers the responsibilities of concert organizers in addressing barcode malfunctions as part of service contracts to consumers. The results of the analysis are expected to contribute to legal understanding of consumer protection in the context of non-functional barcodes on concert tickets. Apart from that, this journal also provides suggestions for improving systems or regulations that can minimize risks and harm consumers in similar situations in the future.